Assessing the use of eDNA metabarcoding to monitor mine site restoration - van der Heyde, Mieke Elisabeth (Curtin University, 2021)
Monitoring restoration is key to assessing the success or failure of methodologies, to improve future restoration, and indicate when further intervention may be necessary. This thesis explores the use of eDNA metabarcoding, a technique to detect biodiversity from DNA, to monitor restoration. Here I evaluate multiple terrestrial substrates as sources of DNA and engage in wide-scale testing to assess the recovery of soil microbes, vertebrates, and invertebrates post mine site restoration